ANALISIS DAMPAK BURUK NARKOTIKA & MEKANISME PEMUSNAHAN BARANG BUKTI NARKOTIKA DI LUBUK LINGGAU - Zainal, Rah; Fitriyani, Fitriyani (LPPM Universitas Bina Insan, 2022)
Narcotics in Indonesia are prohibited from being distributed and used for abuse, this is as intended in the provisions of Article 114 paragraph (2) of Law Number 35 of 2009 concerning Narcotics. Narcotics are used as evidence in a trial based on a court decision that has permanent legal force. Furthermore, the narcotics evidence will be destroyed by the prosecutor's office in accordance with the provisions of Article 91 paragraph (2) of Law Number 35 of 2009 concerning Narcotics. The type of research used is empirical legal research, where empirical legal research is a scientific research model, both qualitative and quantitative, that is empirical-socio-legal in nature, to answer questions and hypotheses that have previously been prepared deductively. The research location is the Asahan District Prosecutor's Office. The mechanism for destroying narcotics evidence at the Asahan District Prosecutor's Office is carried out by involving several related regional government agencies such as: BNN, Health Service, Environment Service where evidence is destroyed by: burning, blending, throwing into the sea. The obstacles in destroying narcotics evidence at the Asahan District Prosecutor's Office are the lack of human resources, inadequate equipment and lack of budget to carry out the destruction of narcotics. Keyword :